Evaluation of antihypertensive efficacy of Losartan + Hydrochlorthiazide versus Telmisartan + Hydrochlorthiazide in patients with stage 1 or stage 2 hypertension: a randomized controlled trial - Sekhon, Manreet Singh; Kaur, Anjleen; Bajaj, Vijay K.; Singh, Harcharan; Gupta, Anita (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Cardiovascular disease (CVD) is the most common contributor of morbidity and mortality in underdeveloped and developing countries including the South Asian countries (including India and Pakistan). Amongst the cluster group of CVDs, Hypertension (HTN) represents the most common cardiovascular risk factor. The aim of this trial was to evaluate of antihypertensive efficacy and effect on biochemical parameters of Losartan + Hydrochlorthiazide versus Telmisartan + Hydrochlorthiazide in patients with stage 1 or stage 2 hypertension with a randomized controlled trial. Methods: This was a prospective, randomized controlled trial of Losartan + Hydrochlorthiazide versus Telmisartan + Hydrochlorthiazide in patients with stage 1 or stage 2 hypertension. The primary endpoint on treatment was analysis of antihypertensive efficacy of these drug combinations. The variables were compared at different time points- baseline, 3 and 6 months. Results: In the present study, 76 patients were enrolled with 38 patients each allocated to each treatment groups. The effect of Losartan 50mg + Hydrochlorthiazide 12.5mg OD was found to be significant on SBP and DBP in both supine as well as sitting position than Telmisartan 80mg + Hydrochlorthiazide 12.5mg OD group at 3 and 6 months. Conclusions: The results on anti- hypertensive efficacy was far better in Losartan 50mg + Hydrochlorthiazide 12.5mg OD group than Telmisartan 80mg + Hydrochlorthiazide 12.5mg OD group.